Temporal and Stochastic Control of Staphylococcus aureus Biofilm Development - Moormeier, Derek E.; Bose, Jeffrey L.; Horswill, Alexander R.; Bayles, Kenneth W. (mBio, 2014)
Biofilm communities contain distinct microniches that result in metabolic heterogeneity and variability in gene expression. Previously, these niches were visualized within Staphylococcus aureus biofilms by observing differential expression of the cid and lrg operons during tower formation. In the present study, we examined early biofilm development and identified two new stages (designated “multiplication” and “exodus”) that were associated with changes in matrix composition and a distinct reorganization of the cells as the biofilm matured. The initial attachment and multiplication stages were shown to be protease sensitive but independent of most cell surface-associated proteins. Interestingly, after 6 h of growth, an exodus of the biofilm population that followed the transition of the biofilm to DNase I sensitivity was demonstrated. Furthermore, disruption of the gene encoding staphylococcal nuclease ( nuc ) abrogated this exodus event, causing hyperproliferation of the biofilm and disrupting normal tower development. Immediately prior to the exodus event, S. aureus cells carrying a nuc :: gfp promoter fusion demonstrated Sae-dependent expression but only in an apparently random subpopulation of cells. In contrast to the existing model for tower development in S. aureus , the results of this study suggest the presence of a Sae-controlled nuclease-mediated exodus of biofilm cells that is required for the development of tower structures. Furthermore, these studies indicate that the differential expression of nuc during biofilm development is subject to stochastic regulatory mechanisms that are independent of the formation of metabolic microniches. IMPORTANCE In this study, we provide a novel view of four early stages of biofilm formation by the human pathogen Staphylococcus aureus . We identified an initial nucleoprotein matrix during biofilm development that is DNase I insensitive until a critical point when a nuclease-mediated exodus of the population is induced prior to tower formation. Unlike the previously described dispersal of cells that occurs after tower development, we found that the mechanism controlling this exodus event is dependent on the Sae regulatory system and independent of Agr. In addition, we revealed that the gene encoding the secreted staphylococcal nuclease was expressed in only a subpopulation of cells, consistent with a model in which biofilms exhibit multicellular characteristics, including the presence of specialized cells and a division of labor that imparts functional consequences to the remainder of the population. In this study, we provide a novel view of four early stages of biofilm formation by the human pathogen Staphylococcus aureus . We identified an initial nucleoprotein matrix during biofilm development that is DNase I insensitive until a critical point when a nuclease-mediated exodus of the population is induced prior to tower formation. Unlike the previously described dispersal of cells that occurs after tower development, we found that the mechanism controlling this exodus event is dependent on the Sae regulatory system and independent of Agr. In addition, we revealed that the gene encoding the secreted staphylococcal nuclease was expressed in only a subpopulation of cells, consistent with a model in which biofilms exhibit multicellular characteristics, including the presence of specialized cells and a division of labor that imparts functional consequences to the remainder of the population.